Análise da fragilidade do baixo curso do Rio Ceará: uma contribuição para a gestão de rios urbanos - Gonçalves, Dayane de Siqueira (2016)
The Brazilian urban growth observed in recent decades has not been accompanied by adequate infrastructure, especially in the most fragile areas such as river banks and ponds. These areas are often occupied by the poorest part of the population that without alternative housing, is susceptible to natural disasters like floods. The rivers are naturally fragile plains, over the years, have become targets of a series of activities that compromise the environmental dynamics of these systems, causing profound changes in matter and energy flows. The lower course of the Ceará River is located on the border of the cities of Fortaleza and Caucaia, and its estuary an Environmental Protection Area due to the great diversity of its natural resources. The pressure that the area is subjected generates a series of impacts from, among other factors, the disorganized and irregular occupation of the river and this little infrastructure. The objective of this work is to seek to understand the relationship between environmental fragility, basic infrastructure and water quality in the lower course of the Ceará River. The analysis follows the methodology of environmental fragility whose basic principle is to define the different levels of fragility of the natural environment and / or modified by human activities. Concerning the water analysis, this was accomplished by checking the Trophic State Index and fecal coliform levels present in the river points. Already in relation to socioeconomic data, these were evaluated from the analysis of the situation of the population living in the vicinity of Ceará River, through the data of census tracts collected in the 2010 Census conducted by IBGE. Therefore, the main objective of this research is to understand the environmental status of the area from the relationship of the three variants mentioned. The results show that through the integrated analysis of the definition of fragility units present in the area of social and environmental diagnostics and results of water sampling, it is possible to have a greater understanding of the environmental quality of the lower course of the Ceará River.